Quality of life in aphasia: differences between fluent and non-fluent aphasic Augmentative and Alternative Communication users - Bahia,Mariana Mendes (2014)
Purpose To investigate and to compare quality of life (QOL) in fluent and non-fluent aphasics. Methods This is a prospective, quantitative, and transversal study. We included 11 stroke patients with aphasia (five non-fluent aphasics augmentative and alternative communication users and six fluent aphasics). Data was gathered from the Stroke Specific Quality of Life Scale (SS-QOL), a structure interview, and The Modified Rankin Scale. Results The non-fluent aphasics presented poorer Rankin and quality of life than the fluent aphasics. The major difference occurred in the fields of language and upper extremity function. The three most affected domains in non-fluent aphasics were language, social roles, and thinking, whereas in the fluent aphasics were personality, social roles, and thinking. All the subjects referred a worse quality of life after stroke. The domains of language and self-care were identified as the most affected after stroke. Conclusion This study demonstrated that, in general, non-fluent aphasics have lower quality of life than fluent aphasics. However, this difference is not homogeneous among the several quality of life domains. Additionally, this research evidences a relationship between aphasia severity and individual functionality, implying impairment in quality of life, especially for non-fluent aphasics.